Three-way complex variant translocation involving short arm chromosome (1;9;22)(p36;q34;q11) in a chronic myeloid leukemia patient - ASIF, MUHAMMAD (Oncol Lett, 2015)
Chronic myeloid leukemia (CML) is a disease of the clonal hematopoietic stem cells caused by a balanced translocation between the long arms of chromosomes 9 and 22. Overall, 90–95% of CML patients present with a Philadelphia (Ph) chromosome t(9;22)(q34;q11) translocation and in addition, variant complex translocations, involving a third chromosome, are observed in 5–8% of CML patients. Cytogenic testing using bone marrow sample was performed and the FISH test was used for the detection of BCR-ABL fusion gene and complete blood analysis of CML patient was also performed. Results of hematological analysis showed the induced values of white blood cells (168,5000/mm(3)) and platelets (300,000/mm(3)) and FISH analysis test showed that 98% cells were positive for BCR/ABL gene translocation. The present study describes a three-way (1;9;22)(p36;q34;q11) Ph chromosome translocation in a 24-year-old female with CML. The patient, who was in the chronic phase of the disease, was treated with daily dose of 400 mg/dl with imatinib mesylateand was monitored constantly at various intervals over a 6-month period. Many studies reported that certain CML patents with variant translocation responded poorly to imatinib. In the current case report, the CML patient exhibited a suboptimal response to imatinib, denoting a poor prognosis.